Comparative Survey of Freedom, 1972-1976 - Gastil, Raymond D. ([Verlag nicht ermittelbar], 1984)
This data collection contains information gathered in five annual surveys that assessed the degree of freedom in 218 nations and dependencies from 1972-1976. The study was carried out under the auspices of Freedom House, New York City. The number of cases with data varies from year to year, due to annexation, amalgamation, or the addition of further territories to the roster. The data include assessments of the political and civil rights of the general population (using a seven-point scale, i.e., 1, most freedom, to 7, least freedom), an overall freedom rating for the country (using a three-point scale, i.e, free, partly free, and not free), and the direction in which this rating appeared to be moving. Surveys after 1972 have added variables that indicate whether a change in the evaluation since the previous survey was due to internal events in the country or to new information about existing conditions. Before 1973, only the presence or absence of change is noted. Thereafter, an increase in the number of coding categories enables the direction of the change to be recorded. The 1976 data include four additional variables applicable to 142 cases and provide information about the system of government and the economy of most of the nations studied. The rationale used in assigning the seven categories on the continuum of most to least freedom can be found in Appendix III of the codebook, including which civil and political rights were considered critical in order for a nation to garner each rating.